A novel MPPT Algorithm Based on MRAC-FUZZY Controller for Solar Photovoltaic Systems - Mahbouba Brahmi; Afef Marai; Hichem Hamdi; Chiheb Ben Regaya; Abderrahmen Zaafouri (Power Electronics and Drives, 2025)
A novel and extremely effective fuzzy Model Reference Adaptive Control (MRAC) based on Maximum Power Point Tracking (MPPT) with a boost converter is presented in this study. It goes into detail on the adaptive gain selection procedure and MRAC design. The paper proposes a simplified fuzzy MRAC process and describes the adaptation gains adjustment using a Fuzzy Logic (FL) subsystem. To test the durability and flexibility of the suggested approach, extensive simulations in MATLAB/Simulink are conducted, considering a variety of scenarios and environmental variables. Findings demonstrate the extreme robustness of the MRAC-Fuzzy MPPT control, with up to 99.98% tracking efficiency. It also keeps the photovoltaic systems operating at or near the Maximum Power Point (MPP), effectively reducing oscillations, improving energy efficiency, and boosting power production.